Studies of Molecular Dynamics and Electronic Structure in Cubic-SiC by Using Density Functional Tight Binding Approach - R.M.A. Khalil; Hussain, Fayyaz; Ahmad Niaz, Niaz (Journal of Materials and Physical Sciences, 2021)
The radiation damage in Silicon-Carbide and its result are presented in this research. The Density Functional Tight Binding (DFTB) approach is used to perform molecular dynamics simulations to implement the DFTB+ code (Elstner et al., 1998). This methodology shows the making and breaking of chemical bonding as well as describes the realistic total energy for the larger systems. Repulsive potentials have been developed to prevent the atoms to stay close to each other during the model of high energy collisions also correctly describe the configurations during the atomic separation within the typical range. The extent and nature of damages are characterized within the collision event up to 10KeV. The band structure of SiC has been studied using minimal basis (sp) as applied in DFTB+. The value of band gap shows that cubic SiC is a large band gap semiconductor material. This value is comparable with the given in literature. Density of states is also calculated by using the tight binding approach. The peaks of spectrum have been compared with the experimental values found in literature.